The interplay between the microbiome and colonic immune system in checkpoint inhibitor therapy - Dehinsilu, Jacob; Sergaki, Chrysi; Amos, Gregory; Fontana, Vanessa; Pirmohamed, Munir (Frontiers in Microbiomes, 2023)
The advent of immune checkpoint inhibitor therapy was a significant step in the development of treatments for cancer. It is, however, a double-edged sword. Immune related adverse events are the result of unleashing brakes on the immune system and affect many patients undergoing checkpoint inhibitor therapy, often being debilitating and occasionally lethal. It has been shown both in mice and in humans that the presence of certain families, genera and species of bacteria are associated with improved responses to checkpoint inhibitor therapy, whereas in their absence the response to therapy is often poor. Recent studies have demonstrated that immune related adverse events to checkpoint inhibitor therapy can be perturbed and perhaps predicted based on the composition and functional capacity of the gut microbiota and parts of the immune system. In the case of colitis associated with immune checkpoint inhibitor therapy, one interesting avenue of investigation is based on the activity of secretory immunoglobulin A (SIgA). Produced by plasma cells, IgA is present in high concentrations at the gut mucosa and is involved in both the maturation and maintenance of the microbiota as well as the development of IBD. Here we summarise the current literature surrounding the interplay between the gut microbiota and response to CPI therapy. Additionally, we overview the colonic immune system, paying particular attention to IgA, as a key component of the microbiota-immune system interaction